Elevating Women in the Workplace The Dual Influence of Spiritual Intelligence and Ethical Environments on Job Satisfaction - Bai, Ali; Vahedian, Morteza; Bai, Mohammad; Ghahreman, Rashin; Piri, Hasan (PT. Riset Press International, 2024)
In today's rapidly evolving workplace, the dynamics of job satisfaction and its determinants have become a focal point of organizational studies. This research offers a comprehensive examination of the nexus between spiritual intelligence and job satisfaction among female employees, with particular emphasis on the moderating role of ethical work environments. The study explores the multifaceted nature of human needs and delves deep into the psychological underpinnings that drive job satisfaction. It elucidates how various tangible and intangible motivators, such as salary benefits and recognition, shape employee attitudes and behaviors. Moreover, the research spotlights female employees' unique challenges and experiences, advocating for a more inclusive understanding of their needs. An extensive review of the literature and empirical analysis culminates in the pivotal finding that integrating spiritual intelligence and ethical considerations within organizational practices can significantly enhance job satisfaction. Such a holistic approach, the paper posits, not only bolsters the well-being and contentment of female employees but also augments overall organizational productivity, retention rates, and morale.